A Case of Tumor Lysis Syndrome Induced by Surgery in Colon Cancer with Multiple Liver Metastases - Yamamoto, Manabu; Iseda, Norifumi; Yano, Hiroko; Tominaga, Yohei; Sugino, Ayako; Kobayasi, Hiroyuki (Archives of Clinical and Medical Case Reports, 2019)
Although tumor lysis syndrome is well described after chemotherapy for non-solid tumors, it is rarely seen or suspected in solid malignancies. Early recognition of this condition is paramount to reduce morbidity and mortality. We report on a case of tumor lysis syndrome induced by surgery in a patient with colon cancer with multiple liver metastases. We also review fifteen cases of diagnosed tumor lysis syndrome accompanying colorectal cancers. Though tumor lysis syndrome is rare in solid tumors, we should realize this possibility in patients with solid tumors of larger volumes, in particular, with enlarged liver metastases.